2020
DOI: 10.3390/jcm9020298
|View full text |Cite
|
Sign up to set email alerts
|

Improved Left Atrial Function in CRT Responders: A Systematic Review and Meta-Analysis

Abstract: Cardiac resynchronization therapy (CRT) is associated with reverse left atrial (LA) remodeling. The aim of this meta-analysis was to assess the relationship between clinical response to CRT and LA function changes. We conducted a systematic search of all electronic databases up to September 2019 which identified 488 patients from seven studies. At (mean) 6 months follow-up, LA systolic strain and emptying fraction (EF) were increased in CRT responders, with a −5.70% weighted mean difference (WMD) [95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Lack of both reverse LV remodeling and decrease in MR severity affects LA hemodynamics and size. The effect of LV remodeling on LA function was described in a meta-analysis by Bytyçi et al, who reported improvement in LA hemodynamics and function in patients responding to CRT [49]. On the other hand, it is known that MR also works in favor of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of both reverse LV remodeling and decrease in MR severity affects LA hemodynamics and size. The effect of LV remodeling on LA function was described in a meta-analysis by Bytyçi et al, who reported improvement in LA hemodynamics and function in patients responding to CRT [49]. On the other hand, it is known that MR also works in favor of AF.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the effect of reverse LV remodeling on left atrial hemodynamics, and improved left atrial function has been demonstrated in CRT responders who are in sinus rhythm. 41 Furthermore, up to 40% of patients indicated for CRT have significant functional mitral regurgitation, owing to combination of LV dyssynchrony and dilatation, and improvement in mitral regurgitation severity has been reported in 23%-49% of patients after CRT in clinical trials. 42 Mitral regurgitation has a complex interaction with AF, and has been associated with poorer outcomes after ablation.…”
Section: Inappropriate Defibrillator Therapiesmentioning
confidence: 99%
“…Reverse left ventricular remodeling is thought be the best predictor for these cardiovascular endpoints. It has been suggested, however, that left atrial reverse remodeling as a possible marker for atrioventricular resynchronization should be included in follow-up examinations [5][6][7]. The amount of reverse remodeling that defines a responder is also a subject of debate.…”
mentioning
confidence: 99%